KEDUDUKAN NOTARIS SEBAGAI DIREKTUR DALAM PERSFEKTIF PERATURAN PERUNDANG-UNDANGAN YANG BERLAKU - Radam , Ady Prasetya (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2017)
This research aims at studying and analyzing the ratio legis of the provisonon the double position of the Notary Publics as stipulated in Artecle 17 of ActNumber 2 of 2012 concerning Notary Public’s Office and analyzing the provision ofArticle 93 paragraph (1) of Act Number 40 0f 2007 concerning Limited Companyin relation with the position of the Notary Public as Director. This is normativelegal research by conducting library study mainly secondary legal resources. Thisresearch applies statute apporoach by studying all acts and regulations related withthe legal issue being dealt with. The nature of this research perspective analytical,i.e to explain precisely the caharacteristics of an individual, condition/phenomenaof the groups in order to determine the spead of a phenomenon and to determinethe existence of relation between one phenomenon to the order in the society. Theresults of this research are firstly, the ratio legis of the provision on the doubleposition of the Notary Public as stipulated in Article 17 of Act Number 2 of 2014concerning Notary Public’s Office is to avoid double position which may lead toconflict of interest. If a the Notary Public has doble position as director, it is clearthat there are differences the Notary Public of authorities, and this may cause abuseof power. Secondly, a Notary Public holds a position as a director as stipulated inArticle 93 paragraph (1) of Act Number 40 of 2007 concerning Limited Company isnot possible. Articles 17 of Act Number 2 0f 2014 concerning Notary Public’s Officeprohibits double position. Limited Company Act does not explicity mentions aboutdouble position in a Limited Company, but it is clearly done because the tasks andauthorities of a Notary Public and a Director are very distict and double positionmay bring about conflict of authorities.